New Output Gap Estimates for Assessing Fiscal Policy with Lessons for Euro Area Reform - Heikki Oksanen (Center for Economic Studies and ifo Institute (CESifo), 2018)
Output gaps (OG) identify economic cycles and the cyclical and structural components in government budget balances. A new simple method for estimating OGs is presented here. The new results are more transparent than those published by the leading economic policy institutions. - The retroactive changes to the OGs as such do not indicate that they would have been incorrect. Instead, they naturally depend on what will happen afterwards, including changes in the fiscal and other policies conducted. - Fiscal policy in the euro area was tight in 2012-13, contributing to an unexpected fall in the GDP. Fiscal policy has generally amplified cycles in the euro area, except in 2009. - Procyclicality is caused by short-sighted fiscal discipline stemming from the mistrust among the member states. Policy reforms should focus on long-term sustainability and diminishing conflicts and mistrust. The numerous reform proposals should be assessed under two key criteria: (1) reducing mistrust across the members and (2) implementation without changes to the EU Treaty. Focussing on long-term sustainability meets them both.
Keywords: E42; E62; H10; 330; euro; fiscal policy; output gaps